TOUCHING GRAIN KERNELS SEPARATION BY GAP-FILLING - Faessel, Matthieu; Courtois, Francis (Image Analysis and Stereology, 2011)
Separation of touching grain kernels is a recurring problem in image analysis. Morphological methods to separatemerged objects in binary images are generally based on the watershed transformapplied to the inverse of the distance function. This method is efficient with roughly circular objects, but cannot separate objects beyond a certain elliptic shape nor when the contact zones are too numerous or too large. This paper presents a gap-filling method applied to the skeleton of the image background as an alternative technique to go further in the fused objects separation process. Open lines resulting from skeletonization are prolonged according to their direction from corresponding end points. If the distance between two lines is smaller than a certain value, their respective end points are connected. Results of combined use of watershed and gap-filling based methods are presented on sample binary images. An example of its use on an particularly complex image containing rice grains shows that it allows to segment up to 90% of the grains when classical watershed methods allow only to segment 25% of the grains. An application to breakage and cracks assessing of parboiled rice kernels is presented.